Scriptural allusions and exegesis in the Hodayot - Hughes, Julie A., 1950- (Studies on the Texts of the Desert of Judah, 2006)
It has long been noted that the Thanksgiving Hymns (Hodayot) from Qumran make extensive use of biblical language. A premise of this study of their use of scripture is that these compositions can best be understood by reading them as poetry. Using insights from the fields of comparative literature and biblical studies it establishes a method for analysis of the poems and for identification and analysis of scriptural allusions. Five poems have been chosen for detailed study. The question is asked, how would a reader familiar with the scriptural traditions of the period interpret these poems and why? The first chapter gives a useful overview of the scholarship to date and indicates the new avenues explored by this study.